2003
DOI: 10.1046/j.1525-1594.2003.00027.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Pulsatile and Nonpulsatile Flow in Microvessels of the Bulbar Conjunctiva in the Goat with an Undulation Pump Artificial Heart

Abstract: This study has three purposes, as follows. The first is to develop a microscopic system to observe the microcirculation of animals implanted with an artificial heart. The second is to investigate the influence of flow pattern change from pulsatile to nonpulsatile on the microcirculation. The third is to study the effects of pulsatility in blood flow on endothelium-derived nitric oxide release in the microvasculature. When the flow pattern was changed from pulsatile to nonpulsatile, the velocity of erythrocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…It has indeed been shown that the absence of pulsatility is associated with capillary fall out, endothelial damage, endotoxin translocation and the production of cytokines, endothelin-1, lactate and catecholamines (2,33,41,42). Interestingly, Sezai et al (33) showed that the increased production of endothelin-1 with nonpulsatile flow starts no earlier than after weaning from cardiopulmonary bypass, simultaneously with impairment of microcirculatory recovery as shown in our investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It has indeed been shown that the absence of pulsatility is associated with capillary fall out, endothelial damage, endotoxin translocation and the production of cytokines, endothelin-1, lactate and catecholamines (2,33,41,42). Interestingly, Sezai et al (33) showed that the increased production of endothelin-1 with nonpulsatile flow starts no earlier than after weaning from cardiopulmonary bypass, simultaneously with impairment of microcirculatory recovery as shown in our investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that pulsatile flow exists at the microcirculation level; and during non-pulsatile perfusion, the flow distribution is not homogeneous when compared with pulsatile perfusion. Baba et al [13,14] observed the microcirculation on the bulbar conjunctiva with a digital high-definition microscope to investigate the different flow patterns on the microcirculation on a goat with a total artificial heart. They believed that pulsatile flow enhances the basal and flow-stimulated endothelin release in microvessels, and that there was a possibility that non-pulsatile perfusion caused microvascular dysfunction, which could become more severe with prolonged non-pulsatile ventricular assist device (VAD) support or permanent non-pulsatile artificial heart implantation.…”
Section: Direct Evidence Of the Pulsatile Effect On The Microcirculatmentioning
confidence: 99%
“…They are linked neurohumourally and hemodynamically (e.g. 2,8,9 Accordingly, the present retrospective study was to investigate changes in PF post-LVAD placement in relation to the haemodynamic changes and their association with survival. 5 Structural and functional alterations of the lungs in HF are well described 5,6 and correlate to HF severity and patient survival.…”
Section: Introductionmentioning
confidence: 99%